2015
DOI: 10.1007/s10157-015-1186-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of novel allelic variants in URAT1 and GLUT9 causing renal hypouricemia type 1 and 2

Abstract: This is the first complex function characterization of non-synonymous allelic variants in patients with renal hypouricemia regarding both GLUT9 isoforms. Our finding of defects in the SLC2A9 and SLC22A12 genes show the following: renal hypouricemia is not restricted to East Asia populations; urate uptake of GLUT9 variants prepared for both isoforms were not significantly different; renal hypouricemia type 2 has more wide clinical variability than type 1; the phenotypic severity of renal hypouricemia is not cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Subjects with heterozygous GLUT9 mutations show a wider spectrum of serum UA levels, ranging from 2.0 to 4.5 mg/dl, whereas FE-UA values range from 3.2 to 21.7% in one study from Israel [16] ; these authors concluded that haploinsufficiency results in mild hypouricemia. The recent report of a 54-yearold Czech woman with a novel heterozygous missense mutation in the SLC2A9 gene, exhibiting low serum UA levels (1.16-1.78 mg/dl) and FE-UA of 17.7%, is in line with this observation; functional study of the identified mutation showed a significant decrease in urate uptake [7] . We have previously summarized the molecular and clinical features of all RHUC2 patients reported until 2014 [8] , and only a few new cases were published in the meanwhile [6,7,17,18] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Subjects with heterozygous GLUT9 mutations show a wider spectrum of serum UA levels, ranging from 2.0 to 4.5 mg/dl, whereas FE-UA values range from 3.2 to 21.7% in one study from Israel [16] ; these authors concluded that haploinsufficiency results in mild hypouricemia. The recent report of a 54-yearold Czech woman with a novel heterozygous missense mutation in the SLC2A9 gene, exhibiting low serum UA levels (1.16-1.78 mg/dl) and FE-UA of 17.7%, is in line with this observation; functional study of the identified mutation showed a significant decrease in urate uptake [7] . We have previously summarized the molecular and clinical features of all RHUC2 patients reported until 2014 [8] , and only a few new cases were published in the meanwhile [6,7,17,18] .…”
Section: Discussionsupporting
confidence: 63%
“…In addition, familial hypouricemia has also been described in patients harbouring homozygous or compound heterozygous mutations in the SLC2A9 gene, which encodes another key player in UA homeostasis, glucose transporter 9 (GLUT9; RHUC2). Patient ethnicity is diverse and includes Japanese, Chinese, Arab, Ashkenazi-Jewish, Anglo-Saxon, Greek, and Czech; to date, only few Caucasian families with a GLUT9 mutation have been reported [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-six URAT1 variants are currently associated with the hypouricemia phenotype. Functional analysis confirmed in part of these variants impact on urate uptake ability and/or cytoplasmatic expression and localization [7,11,13,14]. However, not all URAT1 allelic variants have effect on decreasing of protein expression and/or function (p.R228E, R477H) [7,11].…”
Section: Discussionmentioning
confidence: 87%
“…A missense variant of URAT1, p.R325W, was tested for urate transport activity using in vitro expression analysis in Xenopus oocytes as previously described [11,13]. Subcellular localization was determined using immunocytochemical analysis.…”
Section: Functional Analysismentioning
confidence: 99%
“…SLC22A12 : p.Gln382Leu was recognized as conservative as well as likely pathogenic in ClinVar, which was in accordance with functional characterization (Wakida et al, ). Besides, the phenotypic severity of hRHUC is not necessarily correlated with function status of the mutants (Mancikova et al, ) and some patients even occur nonrenal complications such as rhabdomyolysis (Chakraborty & Sural, ) and neurological symptoms of posterior reversible encephalopathy syndrome (Fujinaga et al, ; Mou et al, ; Shima et al, ), which altogether implies a complexity of genetic involvement and pathophysiological process underlying the disease spectrum. Primary hypouricemia is a common characteristic of xanthine dehydrogenase (XDH) deficiency (Xanthinuria 1, OMIM #278300) and reduced synthesis of molybdenum cofactor (Xanthinuria 2, OMIM #603592) and hRHUC1 (OMIM #220150) and hRHUC2 (OMIM #612076).…”
Section: Discussionmentioning
confidence: 99%